MAGNETIC HYPERFINE FIELD AT CESIUM IN IRON - Ashworth, C; Back, P; Ohya, S; Stone, N; White, J (Kluwer Academic Publishers, 1990)
We report temperature dependence of nuclear orientation (NO), and the first observation of NMR/ON on Cs in iron.132, 136Cs were implanted at room temperature into polycrystalline and single crystal iron. NO values for the (average) magnetic hyperfine field Bhf (Cs Fe) are close to 34T, intermediate between the value of 40.7T found in on-line samples made at mK temperatures and the NMR/ON value of 27.8 (2)T. The latter studies. The site/field distribution is briefly discussed. © 1990 J.C. Baltzer A.G., Scientific Publishing Company.